Secukinumab efficacy on resolution of enthesitis in psoriatic arthritis: pooled analysis of two phase 3 studies - Coates, Laura C.; Wallman, Johan K.; McGonagle, Dennis; Schett, Georg; McInnes, Iain B.; Mease, Philip J.; Rasouliyan, Lawrence; Quebe-Fehling, Erhard; Asquith, Darren L.; Fasth, Andreas E.R.; Pricop, Luminita; Gaillez, Corine (Arthritis Research & Therapy, 2019)
BACKGROUND: Enthesitis is one of the psoriatic arthritis (PsA) domains. Patients with enthesitis are associated with worse outcomes than those without enthesitis. The effect of secukinumab on the resolution of enthesitis in patients with PsA was explored using pooled data from the FUTURE 2 and 3 studies. METHOD: Assessments of enthesitis through week 104 used the Leeds Enthesitis Index. These post hoc analyses included resolution of enthesitis count (EC = 0), median time to first resolution of enthesitis (Kaplan-Meϊer estimate), and shift analysis (as observed) of baseline EC (1, 2, or 3-6) to full resolution (FR), stable (similar or reduction of EC), or worse (EC > baseline). Efficacy outcomes (ACR, PASI, HAQ-DI, SF-36 PCS, and DAS28-CRP) were assessed in patients with or without baseline enthesitis. Results are reported for secukinumab 300 and 150 mg in the overall population and by prior TNFi treatment. RESULTS: A total of 65% (466/712) of patients had baseline enthesitis. In the overall population, FR was achieved as early as week 16 in 65% (300 mg) and 56% (150 mg) versus 44% (placebo) patients, with further improvements to 91% (300 mg) and 88% (150 mg) at week 104. The majority (89%) of patients without enthesitis at baseline maintained this status at week 104. Median days to resolution of EC were shorter with secukinumab 300 and 150 mg versus placebo (57 and 85 vs 167 days, respectively). In patients with EC of 1 or 2, shift analysis from baseline to week 24 showed that more patients achieved FR with secukinumab 300 mg and 150 mg versus placebo, whereas no difference between secukinumab and placebo was shown in the more severe patients with EC of 3-6. Increases in proportions of patients with FR were observed with secukinumab irrespective of the severity of EC from baseline to week 104. Improvements in efficacy outcomes were similar in patients with or without enthesitis treated with secukinumab 300 mg. CONCLUSION: Secukinumab provided early and sustained resolution of enthesitis in patients with PsA over 2 years. Secukinumab 300 mg provided higher resolution than 150 mg in patients with more severe baseline EC and showed similar overall efficacy in patients with or without enthesitis. TRIAL REGISTRATION: FUTURE 2: ClinicalTrials.gov, NCT01752634 (date of study registration: December 19, 2012), and EudraCT, 2012-004439-22 (date of study registration: December 12, 2012) FUTURE 3: ClinicalTrials.gov, NCT01989468 (date of study registration: November 21, 2013), and EudraCT, 2013-004002-25 (date of study registration: December 17, 2013).
CRIS-Team Scopus Importer:2019-12-17
Keywords: Anti-TNF; Biologics; Enthesitis; Interleukin 17A inhibitor; Psoriatic arthritis; Secukinumab